PSYCHOPEDAGOGICAL INTERVENTIONS FOR CHILDREN WITH ASD IN REGULAR SCHOOLS - Alves dos Santos , Sirlei (Revista Gênero e Interdisciplinaridade, 2026)
This article addresses psychopedagogical intervention strategies aimed at the cognitive, social, and emotional development of children with Autism Spectrum Disorder (ASD) in the context of mainstream schools. The research used a bibliographic approach, based on specialized sources, to identify inclusive methods, evaluate their efficiency, and suggest practices adapted to the needs of these students. It was found that the inclusion process faces significant challenges, such as limitations in curricular adaptation, lack of teacher training, and social obstacles. Psychopedagogical interventions, when supported by specialized professionals and integrated with families, proved effective in improving learning and social interaction. It is concluded that promoting inclusive education for children with ASD requires continuous collaboration, personalization of pedagogical practices, and public policies that ensure equality and respect for diversity.